Penggantian Biaya Pemanggilan Saksi Berdasarkan Pasal 229 KUHAP di Kabupaten Gowa: Perspektif Hukum Islam - Azizah, Nur; Mujahidah, Nurul; Gunawan, Muhammad Safaat; Sofyan, Sofyan; Mulya A, Muh Alyan (Universitas Islam Negeri Alauddin Makassar, 2023)
The subject matter of this study is the Islamic Law view on Reimbursement of Witness Costs in Fulfilling Summons Based on Article 229 of the Code of Criminal Procedure in Gowa District from an Islamic legal perspective. The type of research used in this study is a type of qualitative descriptive field research, as for the approach used, normative juridical and normative theological approaches, then the primary data sources are interviews conducted at the Gowa Police Station, the Gowa Prosecutor's Office and the community who have been witnesses in solving cases in Gowa district. Both secondary data sources are sourced from books, journals, and other sources related to this research. Data collection methods carried out, namely observation, interviews, documentation and literature studies. The results of the research obtained are that the reimbursement of witness summoning costs in Gowa district has not been carried out in accordance with what is stipulated in Article 229 of the Code of Criminal Procedure. The inhibiting factors are because the budget items given each year only increase by a few percent while the increase in the number of cases that occur and those reported soar every year, and causes the reimbursement of witness summoning costs has not been optimally applied. In Islamic law, the reimbursement of the cost of summoning witnesses is not specifically regulated but in the Qur'an is equated with the granting of the right to all to create justice for human beings.